A Conformal Transmissive Metasurface with Dual‐Band Dual‐Circularly Polarized Conversion and Low Scattering - Zhihao Li; Sijia Li; Chengyuan He; Yuhao Wu; Liqiu Hu; Zhiyun Zhang; Tong Li; Huanhuan Yang (Advanced Physics Research)
Abstract Generally, the existing metasurfaces are periodically or non‐periodically planar micro‐structures, which hardly satisfy the practical applications such as stealth aircraft, carrier and so on. In order to meet the application, a conformal transmissive metasurface are proposed with multi‐function of converting linear polarization into dual‐circular polarization in dual‐band and low scattering for incidences. The metasurface composed of a non‐metallic dielectric material of polyvinyl chloride and the ultra‐thin conventional material to achieve a flexible configuration. The mechanism is illustrated by the characteristic parameters, electric field distributions, and equivalent circuit. The simulated results demonstrate that the metasurface can transform y‐polarized waves into right‐handed circularly polarized waves in 6.8–10.3 GHz and to left‐handed circularly polarized waves in 18.77–21.15 GHz, while vice versa for x‐polarized waves. Additionally, the conformal metasurface shows an excellent scattering section reduction in operational frequency and that above 10 dB can be realized as the frequency increases. A conformal metasurface sample is fabricated by the printed circuit board (PCB) and 3D printing technology, which is measured in a microwave anechoic chamber that conforms to the simulated results. The conformal transmission metasurface holds significant promise for applications in radomes and electromagnetic shielding.